The Susceptibility of Aedes aegypti In Dengue Endemic Areas, Tegal, Central Java Indonesia - Irfan Kresnadi; Bany Faris Amin; Haekal Ariq; Viharsyah Aulia Akbar; Rawina Winita; Ridhawati Syam; Lisawati Susanto; Nurhadi Eko Firmansyah; Heri Wibowo (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2021)
Tegal district is a dengue-endemic area. One of the strategies to control Ae. aegypti is the use of insecticides. The determination of insecticide resistance in a dengue-endemic area is useful for supporting policies for Ae. aegypti control program. The aim of this study is to determine the susceptibility of Ae. aegypti in Tegal district, Central Java. Aedes aegypti larvae were collected from June to July 2018. Susceptibility bioassay of Ae. aegypti larvae against temephos and Ae. aegypti female against permethrin were conducted refers to the WHO protocol. The susceptibility of Ae. aegypti was interpreted based on WHO protocol as well. The mortality of Ae. aegypti larvae were at 0.025 ppm by 90%. The LC50 at 0.0005 ppm, and LC99 at 1.1037 ppm, respectively. The mortality rate of Ae. aegypti against permethrin was 26%. The LT50 at 6611.636 minutes, and LT99 at 5958807.272 minutes, respectively. The susceptibility of Ae. aegypti larvae were possible resistant but adult Ae. aegypti was resistant.